Tests on reinforced concrete beams and culvert sections - Scholz, Walter T.; Shattuck, Earl Locke; McClaskey, Edward Louis; Kupper, Edward Rudolph (My University, 1907)
Introduction: Reinforced concrete is a building material used in construction work, and consists of a skeleton work of metal embedded in a mass of concrete or cement mortar. Iron rods have been used to tie together and strengthen masonry structures for hundreds of years. Cut stone and ruble masonry do not adapt themselves to the use of iron or steel to take care of the tensile strains, hence not until the advent of modern concrete do we find masonry structures having a metal reinforcement. The first exhibition of reinforced concrete was at the World's Fair at Paris in 1855. The exhibit was a small row boat, reinforced with wire netting. F. J. Momir was the first man to take out patents covering the use of reinforced concrete. His countryman did not appreciate his discoveries and the Germans were the first to develop this form of construction. In these tests an endeavor has been made to compare as nearly as possible the relative strength of beams reinforced with different kinds of reinforcing bars and the strength of the arch (both plain and reinforced) and box form of culverts.
Citation: Scholz, Walter T., Shattuck, Earl Locke, McClaskey, Edward Louis, and Kupper, Edward Rudolph. Tests on reinforced concrete beams and culvert sections. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Reinforced Concrete; Construction Materials; Material Strength; Material Testing; Theses